2021
DOI: 10.1055/s-0041-1731765
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Prolonged Drain Use Following Autologous Breast Reconstruction

Abstract: Background Surgical drains are routinely used following autologous reconstruction, but are often cited as the leading cause of peri-operative discomfort. This study defined routine drain use duration and assessed the risk factors for prolonged breast and abdominal drain use during microvascular breast reconstruction, measures which have never previously been defined. Methods Patients who underwent an abdominal microvascular free flap were included. Demographics, comorbidities, and operation-related c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Dinis et al found BMI to be an independent risk factor for increased drain time. 36 DelMauro and Moon found no correlation between BMI and perforator diameter. 37 Additionally, NSQIP only reflects outcomes for 30 days postoperation, which limits understanding of long-term outcomes relating to obesity.…”
Section: Discussionmentioning
confidence: 92%
“…Dinis et al found BMI to be an independent risk factor for increased drain time. 36 DelMauro and Moon found no correlation between BMI and perforator diameter. 37 Additionally, NSQIP only reflects outcomes for 30 days postoperation, which limits understanding of long-term outcomes relating to obesity.…”
Section: Discussionmentioning
confidence: 92%
“…16 Furthermore, recent findings regarding patient-related factors contributing to prolonged drain duration, such as hypertension and elevated body mass index, may be utilized to establish preoperative goals for patients. 17 While preoperative optimization is valuable in any setting, this may serve as another point of discussion between patients and providers, given the apparently tangible concerns for prolonged indwelling drains and SSI as noted by our study. Of note, recent data suggest the safety and efficacy of drainless donor site closure in autologous breast reconstruction, which may further mitigate concerns for prolonged indwelling drains.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, drains are also a known source of discomfort and dissatisfaction for DIEP flap patients, particularly for those with higher body mass index. 29 Further studies are needed to evaluate how prolonged drainage can be avoided or tailored to improve patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%